О различии словообразовательной структуры слов с идентичным морфемным строением (на материале двукорневых имен существительных и прилагательных со словообразовательным/формообразовательным суффиксом) - Ясудавичюте, Роже (Kalbotyra, 1989)
In the present paper an attempt is made to identify derivational patterns of two-root nouns and adjectives ending in derivational or functional suffixes. Being identical on the morphemic level they differ derivationally. Among nouns compounds proper prevail, while in the class of the adjective compound derivatives c ined after the patterns “/word combination/ + -ed” and /word combination/ + adjectivation” are the most common. The pattern “/word combination/ + adjectivation” has been suggested to substitute N + PI,II. The latter seems inadequate because having a verbal as its second constituent it cannot form adjectives.